FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR SAYURAN DI KABUPATEN KAIMANA PROVINSI PAPUA BARAT - Obadja Andris; Dwidjono H Darwanto; Sri Widodo (Agric, 2014)
Vegetables Vegetables are very important as the counterweight of nutrition and vitamins for human body. Until now, Indonesia is still importing vegetables from other countries. The same circumstance also occurred in West Papua province. In Kaimana district, the supply of vegetables was imported from North Sulawesi. Meanwhile, the import process at the national level took place through a formal import mechanism. This study seeks to determine what factors are thought to influence the volume of vegetables import in Kaimana district. By using the OLS method, it was found that the purchasing price of the imported vegetables is a decisive factor influencing the import process. Vegetables selling price, age of importing traders, number of traders’ family members as well as consumers’ disposable income are not significant to prompt import.